Asupan Lemak dan Ekspresi Gen eNOS3 Alel Glu298Asp pada Penderita Hipertensi Etnik Minangkabau - Delmi Sulastri; Lipoeto NI; Nasrul Zubir; Jamsari Jamsari (MEDIA MEDIKA INDONESIANA, 2011)
ABSTRACTIntake of fat and Gen eNOS3 Alel Glu298Asp expression in hypertensive Minangkabau personsBackground: eNOS 3 gene is one of the important genes which is related to the high prevalence of hypertension essensial. This gene expresses the nitric oxide synthase (NOS) enzyme which regulates the synthesis of nitric oxide (NO) in human body.Methods: A research has been done on hypertensive and normotensive patients aged 30-65 years old. The main purpose of this research was to evaluate the association of fat intake on eNOS3 gene Glu298Asp allel expression in hypertension subjects in Minangkabau ethnicity. One hundred thirty subjects had been interview about their eating habits, and measured their omega-3, eNOS3 gene and NO plasma level. The data were analysed with t-tes and chi-square.Results: The hypertensive’s plasma NO concentration was 26.91±15.40 μM/L and normotensive’s was 25.79±15.04 μM/L. 52.5% of the hypertensive subjects and 47.5% of the normotensive has eNOS3 gene heterozygotes GT allele. Mean rates for total fat, SFA, MUFA and PUFA consumption of hypertensive subjects are 28.05±6.57%, 12.31±4.21%, 4.21±1.79%, 3.77±1.97% and normotensive are 30.14±13.98%, 12.58±4.22%, 4.40±2.22%, 4.00±1.96%. Mean rate for plasma omega-3 concentration of hypertensive subjects is 14.45±0.10μg/dL and normotensive is 14.49±1.00 μg/dL. There is significant relationship between omega-3 with NO plasma level on hypertension with GT heterozygote alleles.Conclusion: In hypertensive patients with GT heterozygote alleles, only omega-3 plasma is associated with NO2 plasma.Keywords: Essensial hipertension, eNOS3 gene, NO plasma levelABSTRAKLatar belakang: Gen eNOS3 alel Glu298Asp merupakan salah satu gen yang berhubungan dengan kejadian hipertensi esensial. Kemampuan Gen eNOS3 alel ini untuk mensintesis enzim nitric oxide synthase (NOS) berkurang sehingga sintesis nitric oxide (NO) menurun.Metode: Penelitian pada subyek hipertensi dan normotensi berusia 30-65 tahun bertujuan untuk melihat hubungan asupan lemak dengan ekspresi gen eNOS3 alel Glu298Asp. Seratus tiga puluh subyek, diwawancara pola makannya lalu dilakukan pemeriksaan kadar omega-3 dan omega-6 plasma, gen eNOS3, serta kadar NO plasma. Data yang diperoleh dianalisis menggunakan uji T dan chi-square.Hasil: Kadar NO plasma subyek hipertensi adalah 26,91±15,40 μM/L dan normotensi 25,79±15,04 μM/L. 52,5% subyek hipertensi dan 47,5% normotensi mempunyai polimorfisme gen eNOS3 alel heterozigot GT. Rerata persentase asupan lemak total, ALJ, ALTJT, ALTJG pada subyek hipertensi adalah 28,05±6,57%, 12,31±4,21%, 4,21±1,79%, 3,77±1,97% dan pada subyek normotensi adalah 30,14±13,98%, 12,58±4,22%, 4,40±2,22%, 4,00±1,96%. Rerata kadar omega-3 plasma subyek hipertensi adalah 14,45±0,10 μg/dL dan normotensi 14,49±1,00 μg/dL. Terdapat hubungan kadar omega-3 dengan NO plasma pada penderita hipertensi dengan alel heterozigot GT.Simpulan: Pada penderita hipertensi dengan alel heterozigot GT, hanya omega-3 plasma yang berhubungan dengan kadar NO2 plasma.